Geology of the West Yamato Nunataks, East Antarctica - Kazuyuki SHIRAISHI (National Institute of Polar Research, 1975)
Seven nunataks, provisionally named the West Yamato Nunataks, located at 30 km southwest of A group of the Yamato Mountains were briefly investigated by the present author in 1973. The heighest peak is 2,282m above sea level but the relative height from the ice surface is only 150m. The rocks exposed in the nunataks are similar to those of the Yamato Mountains except the fact that no charnockitic rocks are found. Hornblendebiotite gneiss is developed in the northernmost nunatak, while granitic gneiss is distributed in the other nunataks. Metabasites, granitic dykes and pegmatites occur throughout the whole area. The occurrences of these gneisses as well as the structural characteristics may suggest a close geological relation between this area and the Belgica Mountains located about 150 km southwest of these nunataks.